Житло пізньосередньовічного часу з Глинського археологічного комплексу - Пуголовок, Ю.О. (Археологія і давня історія України, 2021)
Стаття присвячена введенню до наукового обігу
житлової споруди з території Глинського археологічного комплексу. Подається опис конструктивних особливостей будівлі, аналізуються знахідки виробів з глини, кольорових металів та заліза. The article is devoted to the publication of a dwelling
from the territory of Hlynsky archaeological complex.
The site occupies the cape-like remains of the right root
bank of the Vorskla River. Covering an area of over
14 hectares, of Horodyshche, Kripost, Pansky Yarok,
Tarasivka, Levadnyukova Hora tracts. The complex
includes the Big and Small hillforts, fortified and unfortified
settlements, and burial mounds.
One of the interesting objects discovered in 2009
is the recessed part of the dwelling of the late Middle
Ages. Despite its partial preservation, this object
is still quite an informative. Housing probably belongs
to the buildings with a cold basement and has signs
of log construction of the walls. The absence of pillar
pits and the presence of a vestibule-entrance lead to
this opinion. The furnace was most likely located on
the upper tier. This is evidenced by the concentration
of baked clay and coal at the boundary of the upper
and lower layers of dwelling filling. Similar dwellings
are known from the excavation of Dmytro Berezovets
in the settlement Stan 2, near Putivl. Also, such buildings
are discovered in the settlements of Komarivka
and Ozarichi.
The ceramic complex from the dwelling is represented
mainly by fragments of coockingware and a small
amount of tableware. The forms of coockingware have
certain analogies with vessels from the Ozarichi settlement
and Putivl (Gorodok). However, some pots, such
as those with rectangular rim, were discovered for the
first time. Individual finds quite clearly characterize
the material culture after the Mongol invasion. The coexistence
of things of the Kievan Rus and later period
is traced.
The saturation of the house with ashes and coals
indicates that the house burned down. Dating of the
object is enclosed within the limits of XIV century.